Effects of Detached Mindfulness on Patients with Obsessive-Compulsive Disorder - Atmaca, Murad; Tabara, Muhammed Fatih; Gurok, Mehmet Gurkan (Aves, 2024)
Objective:The objective of this study was to evaluate the effectiveness of detached mindfulness (DM) in patients with obsessive-compulsive disorder (OCD). Methods: Seventeen adult patients with OCD, who were receiving psychotropic medication, were included in the study. M.A., a qualified metacognitive therapist at the Metacognitive Therapy Institute in Manchester, conducted DM therapy. The Yale -Brown Obsession Compulsion Scale (Y-BOCS) and the Beck Depression Inventory (BDI) were used to monitor clinical progress. Results: The mean Y-BOCS scores at baseline and the end of the study were 25.29 +/- 5.70 and 13.53 +/- 3.41, respectively, and a paired t -test analysis revealed a statistically significant difference between baseline and end-of-treatment scores (P<.001). The homework practices were also assessed in sessions 2, 3, and 4. The mean homework scores at the second, third, and fourth homework sessions were 8.70 +/- 1.10, 8.00 +/- 0.79 and 8.20 +/- 1.1, respectively. The DM homework completion rate was at an acceptable level. Conclusion: In conclusion, our study has shown that the DM technique, one of the main techniques used in metacognitive therapy, is significantly beneficial in patients with a certain degree of severity. We are of the opinion that supportive studies with larger sample sizes are necessary for the demonstration of efficacy in patients with significant treatment resistance.
Keywords: Obsessive-compulsive disorder; detached mindfulness; obsession